Mature Cystic Teratoma with Neuroendocrine Tumor — Case Report - Tufail Ahmad Khan; Madiha Amin; Aneeta Singh; Anuja Sharma; K.C Goswami; Sujeet Bhat (JK Science)
Presacral tumors are extremely rare tumors in adults. Such lesions are often found incidentally. The strange presentation of lesions in the pre-sacral space and the ambiguity of its clinical presentation makes it difficult to establish its diagnosis as the first possibility. Given that several germ lines converge in this presacral space, it is possible to find a variety of lesions, one of the rarest being neuroendocrine tumors. We present a case of 34-year-old female diagnosed with pre-sacral mass that was surgically resected, with histologic studies showing a mature cystic teratoma with neuroendocrine tumor.